N4-Acetylcytidine Of Circxpo6 Triggers Mapk Pathway To Promote Pulpitis - Lin, Li (International dental journal, 2025)
Although N4-acetylcytidine (ac4C) modification affects the stability of mRNA, and lncRNA, and regulates miRNA production, it is unknown whether it exists in circular non-coding RNAs (circRNA), and the molecular mechanism on circRNA remains elusive. We performed circRNA microarray assay to reveal the expression patterns of circRNA involved in pulpitis. circXPO6 was identified and verified as a critical factor by qRT-PCR in pulpitis. The gain- and loss-of-function studies were performed to investigate the biological role of circXPO6 in regulating pulpitis progression. By combining the analyses of ac4C-RIP (acRIP) and NAT10-RIP, we found a critical ac4C modification of circXPO6. In addition, through nuclear cytoplasmic separation, acRIP, and acetylation mutant construct experiments, the impact of circRNA acetylation levels on circRNA self-function was analyzed to explore its potentiality in the progression of pulpitis. Herein, we identified ac4C modified circRNA, circXPO6, upregulated in pulpitis tissues, and promoted the inflammatory response in pulpitis. We further reveal that NAT10 contributed to the ac4C modifications of circXPO6 in pulpitis, indicating that the expression of circXPO6 was regulated by NAT10 in an ac4C-acetylation-dependent manner. Importantly, the inhibited ac4C modification of circXPO6 increases export to the cytoplasm in pulpitis, further activating the p38MAPK cascade pathway, ultimately accelerating the progression of pulpitis. Consequently, this study highlights that the ac4C modification of circXPO6 modulates cytoplasmic export and triggers p38MAPK pathway to promote inflammatory response in pulpitis and proposes a promising strategy to alleviate the development of pulpitis.